2022
DOI: 10.1016/j.omto.2021.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial delivery of synthetic mRNA to suppress glioblastoma

Abstract: Owing to messenger RNA's unique biological advantages, it has received increasing attention to be used as a therapeutic, known as mRNA-based gene therapy. It is critical to have an ideal strategy of mRNA gene therapy for glioma, which grows in a special environment. In the present study, we screened out a safe and efficient transfection reagent for intracranial delivery of synthetic mRNA in mouse brain. First, in order to analyze the effect of different transfection reagents on the intracranial delivery of mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…However, screens of large libraries have identified few materials that deliver mRNA outside of the liver and spleen ( 8 , 20 22 , 34 ). Alternative administration routes can circumvent this issue, as has been demonstrated by our laboratory ( 35 ) and others ( 30 ) for mRNA delivery to organs including the heart ( 36 ), brain ( 37 ), and lungs ( 38 , 39 ). Extrahepatic mRNA delivery can also be achieved by incorporating charged amphipathic phospholipids, which shifts protein expression away from the liver to the spleen or lungs ( 40 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, screens of large libraries have identified few materials that deliver mRNA outside of the liver and spleen ( 8 , 20 22 , 34 ). Alternative administration routes can circumvent this issue, as has been demonstrated by our laboratory ( 35 ) and others ( 30 ) for mRNA delivery to organs including the heart ( 36 ), brain ( 37 ), and lungs ( 38 , 39 ). Extrahepatic mRNA delivery can also be achieved by incorporating charged amphipathic phospholipids, which shifts protein expression away from the liver to the spleen or lungs ( 40 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. mRNA vaccines inhibit tumor growth on its size and weight in mice [16] The evaluation of in vitro test from the present study showed TransIT-mRNA injection obtained a longer in vivo half-life and caused little inflammation response than the other, and the optimized dose concentration of 1 μg/20 μL (mRNA/TransIT-mRNA). Additionally, the synthetic red fluorescent protein (RFP) mRNA served as the brain localizer for precise mRNA delivery inside the brain.…”
Section: Clinical Trial From Hubei Medical University On Murine Modelmentioning
confidence: 64%
“…Among all potent DCs (Dendritic cells) electroporated with synthesized mRNA for use in immunotherapy is now the primary reagent chosen to deliver transfection of mRNA as it shows safety in patients with malignancy [13]. The mRNA gene fragment can function on both stationary and proliferating cells without endangering the host cells through translation towards targeting proteins or peptides in the cytoplasm rather than the nuclei.…”
Section: Mrna Vaccinesmentioning
confidence: 99%
“…They found that TransIT‐mRNA kit showed the highest TRAIL expression in mice. [ 290 ] Nanomedicines can also serve as the transfection agent to deliver mRNA by an intracerebroventricular administration of Lipid NPs (LNPs) encapsulating luciferase mRNA. Luminometry revealed that the LNPs successfully transfected the cells in the mouse brains.…”
Section: Gene Therapy For Cns Diseasesmentioning
confidence: 99%